2020
DOI: 10.3389/fneur.2020.00850
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Acute Stroke Presentation at a Comprehensive Stroke Center

Abstract: Background: COVID-19 has impacted healthcare in many ways, including presentation of acute stroke. Since time-sensitive thrombolysis is essential for reducing morbidity and mortality in acute stroke, any delays due to the pandemic can have serious consequences. Methods: We retrospectively reviewed the electronic medical records for patients presenting with acute ischemic stroke at a comprehensive stroke center in March-April 2020 (the early months of COVID-19) and compared to the same time period in 2019. Stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…A total of 52 studies reporting the impact of the COVID‐19 pandemic on stroke admissions were identified for qualitative synthesis. A total of 32,640 stroke admissions from 29 studies 6‐34 were included in the meta‐analysis (Figure 1) (Supplementary Table S1) based on a similar time frame of the study period and comparison period, of which ratios were derived, depending on each criterion data availability. Compared to the prepandemic period, the mean ratio of stroke admissions during the pandemic was 70.78% [95% CI: (65.02%, 76.54%)] (Figure 2) and the mean ratio of ICH cases was 83.10% [95% CI: (71.01%, 95.17%)] (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 52 studies reporting the impact of the COVID‐19 pandemic on stroke admissions were identified for qualitative synthesis. A total of 32,640 stroke admissions from 29 studies 6‐34 were included in the meta‐analysis (Figure 1) (Supplementary Table S1) based on a similar time frame of the study period and comparison period, of which ratios were derived, depending on each criterion data availability. Compared to the prepandemic period, the mean ratio of stroke admissions during the pandemic was 70.78% [95% CI: (65.02%, 76.54%)] (Figure 2) and the mean ratio of ICH cases was 83.10% [95% CI: (71.01%, 95.17%)] (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“… 163 , 244 In addition, due to fears of contracting SARS-CoV-2, many patients fail to seek prompt medical attention in emergent and urgent situations. 245 , 246 A report from Malaysia found a 65.4% decline in hospitalizations in patients with SLE during the lockdown period compared to 2019 rates. However, the patients with SLE who presented to the hospital in 2020 were significantly sicker when compared to those admitted in 2019 with respect to Systemic Lupus Erythematosus Disease Activity Index (SLEDAI), intensive care unit requirement, and mortality.…”
Section: Ancestral Background Socioeconomic Factors and Indirect Conmentioning
confidence: 99%
“…The important issue is the question of whether there is a decrease in the number of patients with neurological diseases that can be fatal and require rapid treatment, such as stroke. In various studies, it has been reported that the number of cases with severe neurological disease (such as acute stroke) decreased after the pandemic, and there were delays in the application/admission of patients with acute stroke [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%